EXTRACTION AND DISPOSAL OF VALUABLE COMPOUNDS FROM DRIED LEAVES - Ubaydullaeva Saidakhon Bakhromjon kizi (European Science Publishing, 2023)
Mother Nature has always been a treasure trove of resources, offering mankind an abundance of materials and inspiration. Among the many gifts that nature gives us, dried leaves often go unnoticed and undervalued. However, recent innovations and discoveries have shed light on the enormous potential of dried leaves, revealing a world of beneficial products waiting to be exploited. From eco-friendly packaging to herbal medicines, the applications of dried leaves span a variety of industries and provide promising benefits to both the environment and society.
Keywords: Dried leaves, Enhanced Plant, absorption, absorption efficiency, soil pH.